UPAYA PENINGKATAN KEMAMPUAN MEMBACA MELALUI PENGELOMPOKAN TINGKATAN KEMAMPUAN MEMBACA PESERTA DIDIK KELAS II B MIN 1 BARITO SELATAN - Alpiannor Alpiannor (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this study was to find out the steps for learning Indonesian by using a technique of grouping levels of reading ability to improve the reading ability of students in class II B MIN 1 South Barito. The grouping of students consists of 3 groups, namely: Advanced Group, Medium Group and Developing Group. The Advanced Group consists of students who are fluent in reading, the Moderate Group consists of students who are not fluent in reading and the Developing Group consists of students who are not fluent in reading. This study uses a descriptive method by describing/describing the current state of the subject or object of research based on visible facts or as they are. The form of research conducted was Classroom Action Research with the subjects of the research consisting of teachers and 28 students II B MIN 1 South Barito. The research was carried out while the author was supervising class teachers who were conducting lessons on Wednesday, November 23, 2022. Based on the assessment data and the results of interviews with teachers, it is known that the technique of grouping levels of reading ability can gradually improve students' ability to read. This is based on the indicators in the list of grade II B students' reading ability scores on October 12, 2022, and November 21, 2022, indicating a change in students' reading ability scores.